Phosphoglycerol substituents present on the cyclic beta-1,2-glucans of Rhizobium meliloti 1021 are derived from phosphatidylglycerol. - Miller, K J (1988)
The synthesis of periplasmic cyclic beta-1,2-glucans is a property unique to species of the family Rhizobiaceae. For this reason, it is generally believed that these molecules may play an important role in the plant infection process. In the present study, we determined that the cyclic beta-1,2-glucans produced by Rhizobium meliloti 1021 were predominantly anionic in character and contained both phosphoglycerol and succinic acid substituents. In addition, we demonstrated that phosphatidylglycerol was the source of the phosphoglycerol substituents present on these oligosaccharides and that greater than 60% of the total phospholipid turnover in this organism involved this substitution reaction.